Studi kreatifitas gotong royong: model pembelajaran kooperatif tipe STAD untuk mengembangkan karakter gotong royong dalam pembelajaran IPS - Arif Mahya Fanny; Susiloningsih Susiloningsih; Apri Irianto (Journal of Creative Attitudes Culture, 2022)
This study was to examine and describe the use of the STAD type cooperative learning model in social studies learning to develop students' mutual cooperation character. The research method used is a literature study. The conclusion from this study is that the use of the STAD type cooperative learning model in social studies learning can develop student character, especially in relation to the character of cooperation. This is because the STAD type supports students actively working in groups with members of different backgrounds, thus increasing empathy, tolerance and the ability to work together in groups. One of the characters in the Pancasila Student Profile is that mutual cooperation can be accommodated by activities in the STAD type cooperative learning model, namely cooperation. In addition, social studies learning has one of the goals of providing knowledge and attitudes that shape the character of being good citizens in the environment and in society.